Effects of membrane property and hydrostatic pressure on the performance of gravity-driven membrane for shale gas flowback and produced water treatment. (February 2020) - Li, Jialin; Chang, Haiqing; Tang, Peng; Shang, Wei; He, Qiping; Liu, Baicang
Graphical abstract: Highlights: GDM was applied to treat SGFPW of Sichuan Basin with PVDF and PVC membranes. A higher flux and lower EPS fouling of PVDF membrane due to intrinsic properties. Low pressure led open and layered fouling layer with less foulant accumulation. GDM effectively reduced SDI and turbidity of raw water in all cases. Abstract: Hydraulic fracturing of shale gas extraction generates numerous flowback and produced water (FPW), which will cause huge pollution if not properly treated. Gravity-driven membrane with economic advantages was applied as a pretreatment for desalinating this wastewater. The effects of membrane materials (polyvinylidene fluoride (PVDF) and polyvinylchloride (PVC)) with different mean pore sizes, porosities, contact angles, and pure water permeabilities and hydrostatic pressures (40 and 120 mbar) were investigated. The setups were operated for 90 days and the fluxes stabilized at about 0.87–1.00 L/(m 2 h). PVDF membranes with higher price, had 6 % higher stable fluxes than PVC membranes, and the extracellular polymeric substances (EPS) contents in fouling layer of PVDF membranes were 10 %–20 % lower than those of PVC membranes. At higher pressures, the stable fluxes increased by only 8 %, but the total resistances increased by nearly 180 %, and there were more EPS, dissolved organic carbon, Na +, Ca 2+, Mg 2+, Cl − and NO3 − on the fouling layer at 120 mbar. A denser cake layer was formed at a higher hydrostatic pressure, as observed by a scanning electron microscope and energy dispersive spectroscopy. Membrane properties and pressures had no significant effect on permeate quality ( p > 0.05).